Control Over the Activities of Public Administration Bodies (Prosecutor's Office, Police, Local Authorities): Legal Regulation, Administrative, Land, Financial Aspects and Prospects for Development Under the Martial Law of Ukraine - Kalchuk, Oleksii; Davydenko, Viacheslav; Mozghovyi, Oleksandr; Hridina, Nataliia; Radchuk, Anatolii (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The purpose of the study is to consider issues of administrative, land, financial regulation and foreign experience in controlling the activities of public administration bodies (prosecutor's office, police, local authorities). Main content. The main assessment measures are defined to ensure the effectiveness of control measures. This assessment is carried out in the following stages: determination of quantitative and qualitative parameters for evaluating the effectiveness of control; assessment of the competence of the control bodies or evaluation of the effectiveness of internal and external control, etc. Methodology: The methodological basis of the study is comparative legal and system analysis, formal legal method, interpretation method, hermeneutical method, as well as methods of analysis and synthesis. Conclusions. It is concluded that to assess the effectiveness of regulatory authorities, it is proposed to improve the following criteria: quality and completeness, reliability of information received by regulatory authorities; timeliness of control, regularity of control, objectivity of control, simplicity of control measures.